2012
DOI: 10.1097/bsd.0b013e318227b52d
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Shoulder Balance Through Growing Rod Intervention for Early-onset Scoliosis

Abstract: When evaluated separately, single rod technique does improve shoulder balance significantly. For a more definitive evaluation, a comparison study having more patients in both groups is essential.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 13 publications
0
9
0
Order By: Relevance
“…In the beginning, the coronal spinal curvature is more prominent in the posterior part of the scoliosis 35) ; whereas in later stages the posterior spinal sagittal plane begins to gain importance 2,3) . Ignorance of the anterior side of the rib cage leads to postoperative cosmetic failure, physiological distress and increased asymmetry of the breast.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…In the beginning, the coronal spinal curvature is more prominent in the posterior part of the scoliosis 35) ; whereas in later stages the posterior spinal sagittal plane begins to gain importance 2,3) . Ignorance of the anterior side of the rib cage leads to postoperative cosmetic failure, physiological distress and increased asymmetry of the breast.…”
Section: Discussionmentioning
confidence: 98%
“…The thoracic curve is successfully treated with final fusion performed with posterior pedicle screw instrumentation following the treatment of EOS with growing rod. Previously, the spine surgeons had concentrated only on the posterior deformity, rather than the deformity of the anterior chest wall 1,2,5,33,35) . However, when scoliosis patients look in the mirror, they can face cosmetic problems as they encounter asymmetry in the breast and anterior wall of the chest.…”
Section: Introductionmentioning
confidence: 99%
“…They determined that CHD was highly correlated with the clinical evaluation parameters, while CTAD was correlated moderately. Uzümcügil et al .,[ 17 ] evaluated the shoulder balance in early onset scoliosis (EOS) scoliosis patients operated with a growing rod, due to various etiologies. They concluded that the CHD should be the primary parameter to be measured, as it proved to be the best method.…”
Section: Discussionmentioning
confidence: 99%
“…They determined that CHD and CRID were highly correlated with the clinical evaluation parameters, while CTAD was correlated moderately. Uzumcugil et al [7] , evaluated the shoulder balance in EOS scoliosis patients operated with a growing rod, due to various etiologies. They concluded that the CHD should be the primary parameter to be measured, as it proved to be the best method.…”
Section: Discussionmentioning
confidence: 99%
“…These parameters include CHD in two patients, CRID in 7 patients and CTAD in 4 patients. Uzumcugil et al [7] published a report indicating that the single growing rod technique provided better improvement for shoulder imbalance. In our study, the single rod technique, when compared to the dual rod and VEPTR groups, provided greater improvement in shoulder imbalance, however we have found that in Group 3 there have been regression by means of shoulder imbalance.…”
Section: Discussionmentioning
confidence: 99%